Sex identification of neotropical macaws (Ara spp.) from invasive and non-invasive samples (2017)
ABSTRACT: While amplification of the Chromo-Helicase-DNA-binding gene (CHD) from blood and feathers has been used to sex macaws, the performance of non-invasive samples has been poorly explored. We optimized a comprehensive protocol of molecular sexing of macaws (Ara spp.) from blood, plucked feathers and fecal samples, using the 2550F/2718R primers to amplify the CHD gene. This protocol is versatile and useful for studies in both ex situ and in situ settings. We successfully identified the sex of macaws from the three types of tissue. However, we recommend sexing from fresh fecal pellets to minimize physical restriction, stress and risk of injury on animals.